Half-metallic electronic feature and thermophysical properties of the Ba2CoMoO6 perovskite-like cobalt molybdate - Deluque Toro, Crispulo Enrique (2020)
Perovskite-like materials which include magnetic elements have relevance due to the technological perspectives in the spintronics industry. In this work, the magnetic, structural and electronic properties of the Ba2CoMoO6 double perovskite are investigated. Calculations are carried out through the Full-Potential Linear Augmented Plane Wave method within the framework of the Density Functional Theory with exchange and correlation effects in the Generalized Gradient and Local Density approximations, including spin polarization. From the minimization of energy as a function of volume using the Murnaghan’s state equation the equilibrium lattice parameter and cohesive properties of this compound were obtained. The study of the electronic structure was based in the analysis of the electronic density of states, and the band structure, showing that this compound evidences a conductive character for a spin channel and insulation for the other, and presents an integer value for the effective magnetic moment (3.0 μB), which allows it to be classified as a half-metallic material. The effects of pressure and temperature on thermophysical properties such as specific heat, Debye temperature, coefficient of thermal expansion and the Grüneisen parameter were calculated and analyzed from the state equation of the system. The obtained results reveal that, in the low temperature regime, the specific heat at constant volume and pressure presents an analogous behavior to each other, with a tendency to the limit of Dulong-Petit typical of the structures of cubic perovskite type, showing a value of 246.3 J/mol.K at constant volume and slightly higher values at constant pressure. The dependence of the coefficient of thermal expansion, the temperature of Debye and the Grüneisen parameter with the increase in temperature is discussed in relation to other perovskite-like materials.